1984
DOI: 10.1007/bf01973825
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-N-formylhydrazine: A toxic and mutagenic inhibitor of the intestinal diamine oxidase

Abstract: N-methyl-N-formylhydrazine is the first active intermediate of the poison gyromitrin of the mushroom: false morel. This compound is a non-competitive inhibitor of human intestinal diamine oxidase (ID50 = 1.6 X 10(-5) mol/l). This concentration corresponds to less than 5 g of wet weight of mushroom/l. The diamine oxidases from 5 other sources are inhibited in a similar manner. Semicarbazide and aminoguanidine are 10-respectively 1000-fold more potent inhibitors of the human intestinal diamine oxidase. An involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cis-IAA can therefore be properly classified as a selective inhibitor of diamine oxidase. The apparent affinity of cis-IAA for DAO compares favorably with other inhibitors of this enzyme such as aminoguanidine which has an apparent affinity of 1.07 x 10-8 M [13].…”
Section: Action (mentioning
confidence: 94%
See 1 more Smart Citation
“…Cis-IAA can therefore be properly classified as a selective inhibitor of diamine oxidase. The apparent affinity of cis-IAA for DAO compares favorably with other inhibitors of this enzyme such as aminoguanidine which has an apparent affinity of 1.07 x 10-8 M [13].…”
Section: Action (mentioning
confidence: 94%
“…1). The major emphasis of our experiments was focused on the pharmacodynamics of cis-IAA because preliminary data [11] showed that the cis-isomer had a relatively low Ki (1.7 x 10-7 M) for inhibition of DAO [13]. For comparison, the activity of the saturated homolog, imidazolylpropylamine Chemical structures of histamine and the histamine homologs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, N -methyl- N -formylhydrazine (MFH), which is produced during MMH metabolism, undergoes cytochrome P450-regulated oxidative metabolism and, via reactive nitrosamide intermediates, leads to the formation of DNA-damaging methyl free radicals (57). As with MAM and nitrosamines, the O 6 -methylation of guanine can cause liver and kidney lesions (58–63) and tumor formation (62). The risk of long-term adverse effects may be greater in individuals with genetic slow acetylation rates because decreased detoxication (acetylation) of MFH would result in larger amounts of MMH formed from gyromitrin (64, 65).…”
Section: Western Pacific Als/pdcmentioning
confidence: 99%
“…It is found in rapidly proliferating tissues, such as intestinal mucosa and bone marrow. MFH noncompetitively inhibits diamine oxidase in vitro [25]. Inhibition of diamine oxidase can produce histamine concentrations that cause flushing, abdominal pain, nausea, vomiting, diarrhea, and headache.…”
Section: Inhibition Of Diamine Oxidasementioning
confidence: 99%